The contribution of natural light and visibility in the optimization of visual comfort: Case of traditional habitat in Arris dechra - Aksas, Samiha; Fenghour, Abir; Hamouda, Abida (Journal of Architecture and environment of child, 2021)
Understading vernacular humain settlements remains arduous and very complicated. This issue leads to an eronous perception and a bad division of spatial systems. The present work aims to know and understand the source of natural light in traditional habitats presenting practically only blind facades, this poses a problem concerning the way in which we seem to get a sufficient natural lighiting for a visible and confortable habitat while respecting identity of the locality. Through the present research based on observation in-situ, the questionnaire survey and the syntactic study of these traditional dwellings in Arris, we concluded that the courtyard is the source of natural light in these habitats.